Preparation and Electrorheological Properties of Peanut‐Like Hollow Core–Shell Structure TiO2@SiO2 Nanoparticles. Issue 5 (1st February 2021) - Sun, Weijian; Zheng, Haonan; Chen, Yi; Li, Changhao; Wang, Baoxiang; Hao, Chuncheng; Xing, Zhaoliang
Abstract : Although titanium oxide has a high dielectric constant, ordinary titanium oxides are not a good electrorheological (ER) fluid material. Herein, hollow peanut‐like titanium oxide spheres are synthesized by hydrothermal method, and then coated with silicon oxide to form core–shell hollow TiO2 @SiO2 spheres. The structure is characterized by different methods, and the TiO2 @SiO2 composite particles are dispersed in silicone oil to prepare an ER suspension. The ER effect of 10% TiO2 @SiO2 ‐based ER fluid under different electric field strengths is tested, and its performance is analyzed. The results show that the coated particles significantly enhance the current meter performance. The shear stress value exceeds 200 Pa at an electric field strength of 3.0 kV mm −1 . The shear stress, shear viscosity, switching effect, and dielectric behavior of the base ER fluid are studied. And, the cause of this strong ER effect is studied. In the end, it is found that TiO2 @SiO2 peanut‐shaped composite core–shell particles have a good ER effect and which is a kind of ER candidate material with simple preparation and development prospect. Abstract : Peanut‐like hollow core–shell structure TiO2 @SiO2 nanocomposite with a hollow and core@shell structure is synthesized using a two‐step method, which can exhibit smart electrorheological behavior under external electric field.